Acetylene containing 2-(2-hydrazinyl)thiazole derivatives: design, synthesis, and in vitro and in silico evaluation of antimycobacterial activity against Mycobacterium tuberculosis. Issue 14 (21st March 2022) - Maganti, Lakshmi Haritha Bharathi; Ramesh, Deepthi; Vijayakumar, Balaji Gowrivel; Khan, Mohd Imran K.; Dhayalan, Arunkumar; Kamalraja, Jayabal; Kannan, Tharanikkarasu
Abstract : In an attempt to find novel anti-mycobacterial agents, novel acetylene containing 2-(2-hydrazinyl)thiazole derivatives have been synthesized and evaluated against Mycobacterium tuberculosis . Abstract : Mycobacterium tuberculosis resistance to commercially available drugs is increasing day by day. To address this issue, various strategies were planned and are being implemented. However, there is a need for new drugs and rapid diagnostic methods. For this endeavour, in this paper, we present the synthesis of acetylene containing 2-(2-hydrazinyl) thiazole derivatives and in vitro evaluation against the H37Rv strain of Mycobacterium tuberculosis . Among the developed 26 acetylene containing 2-(2-hydrazinyl) thiazole derivatives, eight compounds inhibited the growth of Mycobacterium tuberculosis with MIC values ranging from 100 μg ml −1 to 50 μg ml −1 . The parent acetylene containing thiosemicarbazones showed promising antimycobacterial activity by inhibiting up to 75% of the Mycobacterium at 50 μg ml −1 . In addition, in silico studies were employed to understand the binding mode of all the novel acetylene-containing derivatives against the KasA protein of the Mycobacterium . Interestingly, the KasA protein interactions with the compounds were similar to the interactions of KasA protein with thiolactomycin and rifampicin. Cytotoxicity study results indicate that the compounds tested are non-toxic to human embryonic kidney cells.